Abemaciclib induces G1 arrest and lysosomal dysfunction in canine melanoma cells: synergistic effects with fenbendazole - Se-Hoon Kim; Jun-Yeol Choi; Yoon-Ho Suh; Ki-Hoon Song; Min-Ok Ryu; Kyoung-Won Seo (Frontiers in Veterinary Science, 2025)
IntroductionAbemaciclib, a CDK4/6 inhibitor, is well-established for treating hormone receptor-positive and HER2-negative (HR+/HER2−) human breast cancer by inducing G1 cell cycle arrest. However, its antitumor effects in other cancers, including canine melanoma, remain largely unexplored. Canine melanoma often harbors CDK4/6 copy number gains and cell cycle dysregulation, suggesting it may be a suitable target for abemaciclib.MethodsFive canine melanoma cell lines (CMeC1, KMeC, LMeC, UCDK9M4, and UCDK9M5) were used to evaluate the antitumor effects of abemaciclib. Cell viability and migration were assessed using Cell Counting Kit-8 and wound healing assays, respectively. Cell cycle distribution was analyzed by flow cytometry, and the expression of cell cycle-related genes and proteins was examined using RT-PCR and western blotting. The origin of cytoplasmic vacuoles was investigated using FITC-dextran uptake and V-ATPase inhibitor assays. Impaired autophagic flux was assessed by immunofluorescence detection of p62 accumulation. Synergistic effects with fenbendazole were evaluated using the Highest Single Agent (HSA) synergy scoring method, and in vivo efficacy was assessed in a xenograft model.ResultsAbemaciclib induced G1 cell cycle arrest and altered the expression of cell cycle-related genes and proteins. Autophagy, but not apoptosis, was activated. Vacuolization was observed and suggested to originate from lysosomes, as evidenced by FITC-dextran uptake and V-ATPase inhibitor co-treatment. p62 accumulation indicated impaired autophagy flux. Co-treatment with fenbendazole enhanced cytotoxicity and showed synergistic effects within specific dose ranges. In vivo, abemaciclib alone or in combination with fenbendazole significantly suppressed tumor growth.DiscussionThese findings demonstrate that abemaciclib exerts potent antitumor effects in canine melanoma by inducing cell cycle arrest and disrupting lysosomal function. Its synergistic interaction with fenbendazole suggests a potential combinatorial therapeutic approach for canine melanoma.